MORAL AND ETHICAL TEACHINGS IN THE MANUSCRIPT "TERJEMAH SA'ADATUL-ANAM" BY SAYID USMAN BIN YAHYA : A PHILOLOGICAL STUDY - Eka Kurnia Firmansyah (KABUYUTAN, 2025)
This study discusses the manuscript “Terjemah Sa’adatul-Anam” written by Sayid Usman bin Yahya. This manuscript not only serves as a translation of the Arabic book of its counterpart, “Sa’adatul-Anam”, but also provides a summary that facilitates the dissemination of moral and ethical Islamic teachings. It plays an important role in promoting Islamic values relevant to the social conditions of society, particularly in addressing the issue of separating religious values from social life. This study aims to reveal the language style and writing techniques used by Sayid Usman bin Yahya in the manuscript and to analyze its content. Using a philological approach, this research examines the manuscript textually to understand the accuracy and relevance of meaning within linguistic and social contexts of its time. The research methods include manuscript inventory, physical description (codicology), transliteration, and manuscript translation. The results show that “Terjemah Sa’adatul-Anam” manuscript exhibits uniqueness in language style and writing techniques, while also possessing significant value in terms of conveying Islamic teachings. Sayid Usman bin Yahya applies a translation method that maintains the original meaning while adapting the language to ensure it is easily understood by the target audience. However, it was found that the writing style of this manuscript does not fully conform to the “Pedoman Bahasa dan Sastra Melayu” (Guidelines for Malay Language and Literature) by J.J. de Hollander. This study emphasizes the importance of preserving ancient manuscripts through digitization and further studies of text editions. Comprehensive conservation and in-depth analysis of this work are expected to contribute to philological studies and the intellectual history of Islam in the Nusantara, while also preserving scholarly heritage with significant historical and academic value.